ANALISIS MAKNA TARI JEPIN TALI BUI KALIMANTAN BARAT - Ulan, Ulan; Ismunandar, Ismunandar; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research to dig the interest of young generations to preserve artistic tradition and invite people who love art to especially dance can describe a dance that schilling. Methods used in this research is descriptive method .This research etnokoreologi used the approach. Qualitative research used, with speakers Juhermi Thahir, Kusmindari triwati, Sy .Oesman Alkadrie, Sy.Selamat Joesoef Al-qadrie, Sy .Mansyur Harun .A source of data in this study in the form of words or actions .The data is the result of observation , interviews and documentation. In this study engineering test the validity of the data in the form of extra observation and triangulation of a source of. Data analysis technique research which is to analyse types of activities, the activity process, on activities, discuss by supervising lecturer, summarizing research and analysis dance jepin meaning a rope bui West Kalimantan.The result of this research in the form of a description of the meaning and function of dance dance jepin a rope bui Pontianak. Research activities meaning dance analysis jepin a rope bui that is a meeting with informants, the source of information, as well as artists and cultural meeting first and also to Pontianak sanggar andari observation. The process of analytical work meaning dance jepin a rope bui in kelurahan stone overpass that is a meeting with informants, the source of information,cultural experts and an art jepin dance a rope bui Keyword: meaning dance analysis , meaning a rope bui jepin motion dance